Waiting for love but not forever: Modeling the evolution of waiting time to selfing in hermaphrodites - Blüml, Chantal; Ramm, Steven A.; van Benthem, Koen J.; Wittmann, Meike J. (Frontiers in Ecology and Evolution, 2022)
Although mixed mating systems involving both selfing and outcrossing are fairly common in hermaphrodites, the mechanisms maintaining mixed mating are still unknown in many cases. In some species, individuals that have not yet found a mating partner delay self-fertilization for some time. This ‘waiting time’ to selfing () can exhibit heritable variation between individuals and is subject to two opposing selection pressures: waiting longer increases the density-dependent probability to encounter a mate within that time and thereby the chance to avoid inbreeding depression () in offspring, but also increases the risk of dying before reproduction. It has long been hypothesized that fluctuations in population density and thus mate availability can lead to stable intermediate , but to our knowledge there are so far no quantitative models that also take into account the joint evolutionary dynamics of . We use an individual-based model and a mathematical approximation to explore how delayed selfing evolves in response to density and density fluctuations. We find that at high density, when individuals meet often, evolution is dominated by genetic drift; at intermediate densities, strong causes to increase; and at low densities, is purged and approaches zero. Positive feedback loops drive the system to either complete selfing or complete outcrossing. Fluctuating density can slow down convergence to these alternative stable states. However, mixed mating, in the sense of either a stable polymorphism in , or stable intermediate waiting times, was never observed. Thus, additional factors need to be explored to explain the persistence of delayed selfing.